Sea Level Rise, Radical Uncertainties and Decision-Maker's Liability: the European Coastal Airports Case - Leonid V. Sorokin; Gérard Mondello (Fondazione Eni Enrico Mattei (FEEM), 2016)
Until now, most of the growing climate legal litigations mainly concern environmental associations or victims against energy of energy-users firms or States. However, in a near future, because of exacerbating sudden floods linked to climate change, future litigations could (will) concern infrastructure governance versus private companies. Indeed, sues would (will) concern the financial losses these last ones would (will) endure because the infrastructure managers did not make convenient protection choices in due time. This paper particularly investigates the case of coastal airports at the European level. It insists on the importance of climate scientists divergent opinions about the sea level rise and its consequences for decision-takers concerning their potential legal liability for negligence.
Keywords: K32; Q54; R53; 330; Climate Change; Sea Level Rise; Flood; Airports; Transportation Infrastructures; Legal Liability; Uncertainty